MICROBIAL DIVERSITY ASSESSMENT THROUGH RAPD FINGERPRINTING OF METAGENOMES FROM DIFFERENT DRY TROPICAL ECOSYSTEMS - MONTY KUJUR,; AMIYA KUMAR PATEL, (International Journal of Pharma and Bio Sciences, 2016)
The understanding of microbial diversity and their interactions with biotic and abiotic factors is considered as an integrative measure of soil quality. In order to comprehend the relationships within and between microbial communities, the metagenomic approach based on the whole community DNA extract was used for genetic profiling, which provide valuable information about the microbial community structure in different soil profiles. Genetic diversity assessment was performed between 21 microbial metagenomes isolated from seven different soil profiles using RAPD markers, which revealed higher genetic variability among microbial populations coupled with the evolution of microbial strains evident from the correlation analysis between polymorphic loci with Nei’s genetic diversity. Dendrogram analysis using neighbor joining and STRUCTURE analysis indicated the segregation of 21 metagenomes into six independent clusters. AMOVA indicated the existence of genetic variability among (83%) and within (17%) the microbial populations. The study indicated gradual colonization in microbial populations supporting genetic diversity.